From English to Indonesia: Translation Problems and Strategies of EFL Student Teachers - A Literature Review - Risni Ade Sandra (International Journal of Language Teaching and Education, 2018)
This research articulates problems and strategies in translating text from English as the source text to Indonesia language as the target text. By reviewing and analysing critically mélange of concepts, examples and findings explained in some collected references, it is known that problems in translation mostly are around lexical, grammatical and semantic elements. In the other hand, the strategies used to produce acceptable translation result regarding to the readers’ of target text understanding have to consider aspects such as cultural content, the availability of equivalencies, and the ability to use the monolingual dictionary. This research also try to emphasize and to convince why finding problems and strategies of EFL student teachers in translating text is very prominent to help the mapping of which elements in English language that are still hard to be transmitted back to Indonesia language and how to overcome that problems.